Using Predictive Bayesian Methods to Measure the Probability of Finding Earth- Sized BodiesOne of the ongoing investigations involving NASA and other international agencies is an effort to find earth-like objects in space as they may be candidates for lif - Bloetscher, Frederick (European Journal of Applied Sciences, 2022)
One of the ongoing investigations involving NASA and other international agencies is an effort to find earth-like objects in space as they may be candidates for life. At present, these investigations are being undertaken via telescopic means by looking at changes in light intensity caused by transiting planets. As a result, the data available to make estimates of the number of these relatively bodies is currently limited. One means to find a solution to this challenge is to use the number of objects in our solar system, along with predictive Bayesian methods, to develop a probability distribution for the likelihood of finding “earths” in other solar systems in the galaxy. Predictive Bayesian statistical methods are designed to use limited, uncertain data to develop results. Such an analysis is similar to predicting incident size and probability for such unlikely events as hurricanes, oil spills, health risks from contaminants and train accidents. The result provided a probability curve distribution of the size of planets in the solar system which when integrated to include bodies that are deemed of the size to sustain life, yielded the ratio of earth sized objects per star of just over 3, and the number of Earth-sized objects in the galaxy as most likely 7 x 1011. Finding these planets is a bigger challenge.